2006
DOI: 10.1007/s00262-006-0226-7
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I expression in metastatic melanoma correlates with tumor development during autologous vaccination

Abstract: Our knowledge of the mechanisms underlying tumor-specific immune response and tumor escape has considerably increased. HLA class I antigen defects remain an important tumor escape mechanism since they influence the interactions between tumor cells and specific T and NK cells in the course of malignant disease. We have studied here HLA class I expression in six subcutaneous metastases obtained from a melanoma patient immunized with an autologous melanoma cell vaccine (M-VAX). We report in this paper that HLA cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 28 publications
2
54
0
Order By: Relevance
“…These results are in accordance with previous studies and extend the data reported by Vermeulen and coworkers [13,45] and Koopman et al [14] , who suggested that LOH in the 6p21.3 region occurs early and is frequently observed in cervical carcinogenesis. Moreover, a higher haplotype loss was observed in advanced stages of cervical cancer, supporting the concept that the 6p21.3 region, which carries HLA genes, is unstable during malignant transformation of cells, contributing to the mechanism of tumor escape and metastatic progression [46] .…”
Section: Discussionsupporting
confidence: 56%
“…These results are in accordance with previous studies and extend the data reported by Vermeulen and coworkers [13,45] and Koopman et al [14] , who suggested that LOH in the 6p21.3 region occurs early and is frequently observed in cervical carcinogenesis. Moreover, a higher haplotype loss was observed in advanced stages of cervical cancer, supporting the concept that the 6p21.3 region, which carries HLA genes, is unstable during malignant transformation of cells, contributing to the mechanism of tumor escape and metastatic progression [46] .…”
Section: Discussionsupporting
confidence: 56%
“…After many years of rather modest success with tumor vaccination for melanoma [65], investigators had become pessimistic about its potential clinical benefit. Melanoma tumors are probably also driven by cancer stem cells (CSCs), and melanoma CSCs have greatly reduced MHC-I levels [66,67]. Therefore, the T-cell response elicited by the vaccinating peptides would be expected to have only minor effects on the melanoma CSCs, and thus would not be expected to have long-lasting therapeutic effects due to a reduction of this compartment.…”
Section: Optimization Of T-cell Activitymentioning
confidence: 99%
“…102,104 Clinically, decreased MHC class I expression is associated with melanoma progression, therapeutic failure, and poor clinical outcome. [105][106][107] Interestingly, although suppression of MHC class I expression by melanoma stem cells may enable evasion from CD8 þ T lymphocytes of the adaptive immune response, low MHC class I expression would be predicted to increase their susceptibility to NK cells of the innate immune system, which are normally inhibited by MHC class I molecules. However, it is conceivable that melanoma stem cells may escape NK cells by altering their expression of additional surface molecules, such as NK cell ligands, which have activating or inhibitory effects on NK cells.…”
Section: How Melanoma Stem Cells May Evade and Modulate Host Immunitymentioning
confidence: 99%